Enhanced bleaching treatment: opportunities for immune‐assisted melanocyte suicide in vitiligo. Issue 8 (10th July 2014) - Webb, Kirsten C.; Eby, Jonathan M.; Hariharan, Vidhya; Hernandez, Claudia; Luiten, Rosalie M.; Le Poole, I. Caroline
Abstract Depigmentation in vitiligo occurs by progressive loss of melanocytes from the basal layer of the skin, and can be psychologically devastating to patients. T cell‐mediated autoimmunity explains the progressive nature of this disease. Rather than being confronted with periods of rapid depigmentation and bouts of repigmentation, patients with long‐standing, treatment‐resistant vitiligo can undergo depigmentation treatment. The objective is to remove residual pigmentation to achieve a cosmetically acceptable result – that of skin with a uniform appearance. In the United States, only the use of mono‐benzyl ether of hydroquinone (MBEH) is approved for this purpose. However, satisfactory results can take time to appear, and there is a risk of repigmentation. MBEH induces necrotic melanocyte death followed by a cytotoxic T‐cell response to remaining, distant melanocytes. As cytotoxic T‐cell responses are instrumental to depigmentation, we propose that combining MBEH with immune adjuvant therapies will accelerate immune‐mediated melanocyte destruction to achieve faster, more definitive depigmentation than with MBEH alone. As Toll‐like Receptor (TLR) agonists – imiquimod, CpG, and Heat Shock Protein 70 (HSP 70) – all support powerful Th1 responses, we propose that using MBEH in combination with these agents can achieve superior depigmentation results for vitiligo patients.